Branding and Digital Marketing: The Secret to Making SME Products Better Known and Sought After in Sawaru Village, Indonesia - N. Nurlaela; F. Fitri; Andi Ririn Oktaviani; Erik Rachim; Eka Wijaya Paula (Manunggal Halim Jaya, 2026)
This Community Service (PKM) activity aims to improve literacy and understanding among Micro, Small, and Medium Enterprises (MSMEs) in Sawaru Village regarding the importance of branding in building product image and identity. It also provides practical training in creating attractive, consistent logos, packaging, and brand identities. Furthermore, this activity aims to improve MSMEs' ability to use digital media, such as social media (Instagram and Facebook) and marketplaces (Shopee and Tokopedia), for product promotion and sales. The activity's implementation methods include training, hands-on practice, and mentoring, conducted in a participatory manner involving local MSMEs. The results indicate that the training successfully improved MSMEs' understanding and skills in building branding and implementing more targeted digital marketing strategies. Participants were able to create brand identities, manage digital business accounts, and increase product exposure on digital platforms. This training also demonstrated that design and branding skills do not require high costs or complex technology. By leveraging simple digital tools and local creativity, MSMEs can create professional, competitive brand identities. Technically, this activity also fostered a spirit of collaboration among MSMEs by sharing design and packaging ideas, which serves as crucial social capital for the formation of a creative MSME community in Sawaru Village.